9(2x-1)=3(6x+9)

Simple and best practice solution for 9(2x-1)=3(6x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2x-1)=3(6x+9) equation:


Simplifying
9(2x + -1) = 3(6x + 9)

Reorder the terms:
9(-1 + 2x) = 3(6x + 9)
(-1 * 9 + 2x * 9) = 3(6x + 9)
(-9 + 18x) = 3(6x + 9)

Reorder the terms:
-9 + 18x = 3(9 + 6x)
-9 + 18x = (9 * 3 + 6x * 3)
-9 + 18x = (27 + 18x)

Add '-18x' to each side of the equation.
-9 + 18x + -18x = 27 + 18x + -18x

Combine like terms: 18x + -18x = 0
-9 + 0 = 27 + 18x + -18x
-9 = 27 + 18x + -18x

Combine like terms: 18x + -18x = 0
-9 = 27 + 0
-9 = 27

Solving
-9 = 27

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8ab^3-44ab^2+20ab= | | 20x/2=5x | | 2(-6+2n)=2(3n-(6+5)) | | a^2*b^2+a*b+1/4=0 | | 20x/2=5 | | 145+8x=57+19x | | 0.20x+0.25(70)=24.5 | | 0.5x-0.33333333333333=0.25x-0.2 | | -15x^2-23x+28= | | -8k-4k=35 | | 100x/50x=50x/2 | | -0.33333333333333x+0.5=-0.25x-1 | | 1/4(x+6)=1/6(x+8) | | -0.33333333333333x+0.5=-0.25-1 | | 13x-68=179 | | 12/4x=16x/4 | | X^2+y^2-2ax=0 | | rad(3x+25)=x+7 | | 3x^2-5xy-2y^2= | | 5x+9+6x+3= | | 6/6x=89x/1 | | 3x+5+4x+7=19 | | 6*6x=89x*1 | | -9d+7-6d=-133 | | 2b^2+4b+2=0 | | 3x+2-x=6+5x-3 | | m-1/3=-9 | | 2*5x=5x*6 | | 6x+6+7x+5=115 | | 3*x=7*1x | | 6x+6+8x+7=69 | | -2=-49x(2)-7x |

Equations solver categories